Bloodmoney - Ignatius, David ([S.l.] : Quercus, 2012)
INVISIBLE. They are the American government's most powerful asset, their very existence only known to a handful of individuals. INGENIOUS. An elite unit of deep-cover agents, turning the tide in the war on terror. That is, until they start being exposed, one by one. INFILTRATED. And now a hunt to find the leak, before they all go under.
International Edition.
Keywords: Deception; International relations; Pakistan; Retribution; Revenge; Spy stories; United States. Central Intelligence Agency; Women intelligence officers